Contracting in Vague Environments - Marie-Louise Vierø (Queen's University, Department of Economics, 2006)
This paper shows that a new trade-off arises in the optimal contract when contracting takes place with vague information (objective ambiguity), reflecting that real-world contracting often takes place under imprecise information. The choice-theoretic framework captures a decision-maker`s attitude towards vagueness by his optimism. The new trade-off is between (a) incentive provision and (b) exploitation of heterogeneity that arises endogenously because of the vague environment. Consequently, the optimal contract may distort effort in order to relax incentive compatibility and fully exploit the endogenously created heterogeneity, even when the agent is risk neutral and there is no insurance need in the relationship.
Keywords: D82; D80; D20; D86; 330; contracts; vagueness; optimism; pessimism; incentives; objective ambiguity